ANALISIS PELANGGARAN HAK ATAS PRIVASI DALAM KASUS KEBOCORAN DATA APLIKASI PEDULILINDUNGI: PERSPEKTIF HAK ASASI MANUSIA DI ERA DIGITAL - Eufrasia Bolo; Maria Sofiati Siki; Bunga Triana Lalus; Fadil Masud; Fadil Mas’ud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The advancement of digital technology has triggered significant transformations in the realization and protection of human rights (HR), particularly regarding the right to privacy and personal data security. This article aims to analyze violations of the right to privacy in the case of the PeduliLindungi data breach from a human rights perspective in the digital era. The study employs a descriptive qualitative method using a literature review approach, examining academic literature, national legal policies, and reports from human rights and cybersecurity institutions related to data protection. The findings reveal that weak digital security systems and low ethical awareness in data usage create serious vulnerabilities to violations of citizens’ privacy rights. The PeduliLindungi data leak reflects the fragility of legal protection for personal data despite the enactment of Law No. 27 of 2022 on Personal Data Protection. Additionally, the analysis highlights a dilemma between the state’s need to maintain public security and its obligation to guarantee the right to individual privacy as stipulated in Article 12 of the Universal Declaration of Human Rights and Article 28G of the 1945 Constitution. In the context of digital ethics, the misuse of data and artificial intelligence (AI) algorithms without transparent oversight also poses risks to the principles of justice and non-discrimination. Therefore, this article emphasizes the importance of implementing a human rights by design principle, strengthening public digital literacy, and synergizing legal regulations with AI ethics to safeguard human rights in digital spaces. This study contributes to enhancing digital legal literacy and the development of human rights-based policy designs for national data governance.